1985
DOI: 10.1111/j.1469-8986.1985.tb01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Event‐Related Brain Potentials in Children with Attention and Reading Deficits

Abstract: ERPs were recorded from four groups of children: reading disabled, attentional deficit disorder with and without hyperactivity, and normal controls. Subjects pressed a button to a low probability nonsense syllable (target, p= .168) and ignored all other events, which included a high probability nonsense syllable (nontarget, p= .664) and either low probability (category, p= .168) symbols (Block 1) or 3‐letter words (Block 2). The amplitudes of several late ERP components and the latency of the P3 component were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
2
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(120 citation statements)
references
References 19 publications
9
106
2
3
Order By: Relevance
“…All subjects included in our study complained of poor school performance. Individuals in group A had greater P300 latencies and presented altered SSW and speech-in-noise test results, as also seen in studies on P300 results in children without signs of APD and children diagnosed with APD, in which longer latencies were observed in the group of children with APD [20][21][22][23][24][25] . Significant variability was seen in P300 results, and individuals with lower latency also performed better in AP tests 25 .…”
Section: Discussionmentioning
confidence: 74%
“…All subjects included in our study complained of poor school performance. Individuals in group A had greater P300 latencies and presented altered SSW and speech-in-noise test results, as also seen in studies on P300 results in children without signs of APD and children diagnosed with APD, in which longer latencies were observed in the group of children with APD [20][21][22][23][24][25] . Significant variability was seen in P300 results, and individuals with lower latency also performed better in AP tests 25 .…”
Section: Discussionmentioning
confidence: 74%
“…The question asked was not what the concurrent effect of psychopathology was on P300, but rather would the existence of an internalizing or externalizing disorder during childhood or adolescence alter the P300 growth trajectory. Several previous cross-sectional studies have shown that psychopathological states influence the amplitude of P300 both in children/adolescents (Courchesne 1984;Lincoln and Courchesne 1985;Holcomb et al 1985) and in adults (Bruder et al 1995;Steinhauer et al 1991;Blackwood et al 1987). The developmental course of P300 has not previously been assessed with respect to the presence of psychopathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…10,[57][58][59][60][61][62][63] Overall, no major EEG abnormalities (ie, evidence of seizure activity) were found for children with ADHD. Several investigations reported minor differences in ERPs functioning, including longer latencies at the P3 site, 57 longer latencies of certain waves for brainstem auditory-evoked potentials, 58 more slow waves and fewer ␣-waves, 59 and asymmetry in peak amplitude evoked-response potentials. 10 These findings are variable and do not provide any compelling evidence for a particular EEG pattern for patients with ADHD.…”
Section: Medical and Laboratory Screening Testsmentioning
confidence: 99%